Discriminación de canales cuánticos (2021)
In this work, a comprehensive review of quantum parameter estimation applied to quantum channel discrimination is carried out. First, the fundamentals of information theory about generalized measurements and information coefficients for covariance in parameter determination are reviewed. Subsequently, estimation strategies, among which the variational approach, the analysis from the geometry of the information and the covariant measurements are delved. This set of techniques was used for the discrimination of an exotic dephasing channel, where a behavior of N^-1 was obtained with respect to copies of the system in the average cost formulated for the parameters η and φ describing the channel. A geometrical interpretation of the dephasing behavior of the channel was also provided. Also, future work with collective joint measurements was motivated to address the problem of estimating more than one parameter. Finally, quantum estimation was connected with the determination of experimental variables associated with the application of the channel.--Taken from the Degree Document Format.